Why teach history of economic thought today? (2010)
Shorter undergraduate studies, increasing specialization and the priority of applied research in Economics represent threats for the History of Economic Thought (HET) as an integral part of the training of young economists. There are mostly sociological arguments to reduce or eliminate HET courses and contents to which we try to respond in this text. We advance that HET allows developing valuable skills that might help overcome the criticisms against Economics due to its alleged incapacity to offer solutions in times of crisis and to its fascination with quantification and technique. In this context, HET appears as a space for thought, self-criticism and introspection in which new economists may understand that Economics is a process and not a product giving them the abilities necessary to participate in the extended present of their discipline.